(untitled) (Journal of Pure and Applied Sciences (Science Forum), 2026)
This study investigated the teacher-related factors influencing the integration of language and literature instruction among Junior Secondary School (JSS) students in Niger State, Nigeria. A mixed-methods research design was employed to provide both quantitative and qualitative insights into teachers’ perceptions, instructional practices, and pedagogical challenges associated with language–literature integration. The study involved 144 teachers selected through a stratified multistage sampling technique across the three senatorial zones of the state. Data were collected using structured classroom observation schedules, teacher questionnaires, and student interviews, and subsequently analysed using descriptive statistical tools and thematic content analysis. Findings revealed a significant disparity between teachers’ positive perceptions of the pedagogical value of integration and the extent of its practical implementation in classroom settings. Teachers strongly acknowledged the educational relevance of integrating language and literature for promoting real-life language application, vocabulary enrichment, and higher order cognitive development, with a grand mean score of 4.29. However, reported classroom implementation practices were comparatively lower (grand mean = 3.85), particularly in relation to fostering interactive learning and reducing rote memorisation. Although respondents rated their academic qualifications and English language proficiency highly, lower confidence levels were expressed regarding pedagogical competence in literature-based instructional activities (mean = 3.75) and adequacy of professional training for integrated teaching approaches (mean = 3.62). Major constraints identified include overcrowded classrooms, inadequate literary materials, limited instructional time, and insufficient professional development opportunities. Classroom observations and student interviews further confirmed that language and literature were predominantly taught as separate disciplines, with minimal learner-centred engagement. The study concludes that while teachers recognise the instructional value of integration, inadequate pedagogical preparation and structural limitations hinder effective implementation. The study therefore recommends curriculum revision in teacher education programmes to incorporate specialised training and supervised practical experiences in language–literature integration pedagogy.